Henri Duparc’s Art Songs in the Teaching of French Art Songs in China - Xiaozhong , Wang; Mei, Lim Sin (Journal of Roi Kaensarn Academi, 2024)
Henri Duparc, who was one of César Franck’s students, was a famous French composer of the late nineteenth and early twentieth centuries, especially famous for his French art songs. He created more than 100 pieces in his life, because he had very high requirements for his own works and destroyed those he was not satisfied with. In the end, only 16 vocal art songs were retained. Compared with the French composers of the same period such as G. Fauré and C. Debussy, the number of Duparc’s vocal music works is only a fraction, but he was as famous as these two composers in the field of French art songs. His songs are deep in feeling and rich in artistic influence, such as the nostalgic "Song of Melancholy (Chanson triste)", the complaintive "Sighs (Soupir)" , and the subtle and affectionate "Longing (Extase)", the latter being somewhat modelled on R. Wagner in harmony. "Rothermund’s Manor (Le manoir de Rosemonde)" is a dramatic, strong, distinctive style of work; "Phidylé" is an imitation of a medieval ballad, originally written for mezzo-soprano, with three sections and one overlapping song, the overlapping song is the dominant motif of the whole piece, and its repetition suggests that the mistress of the castle has spent the whole night from sunset and moonrise to dawn waiting for her beloved. Duparc’s most perfect songs are "Invitation to a Journey (L’invitation au voyage)" and "The previous life (La vie antérieure)", composed in C. Baudelaire’s poem, which are full of oriental coloured fantasies and longing for a peaceful life.